Assessment of the Effectiveness of the Use of Personal Protective Equipment by Personnel of Medical Organizations of Various Profiles in the Provision of Medical Care to Patients with COVID-19 - E. V. Kryukov; G. G. Maryin; A. A. Kuzin; A. E. Zobov; M. N. Nasybullin; V. V. Zakurdaev; E. A. Luchnikov; E. A. Medvedeva; A. A. Ploskireva; K. A. Zykov; O. A. Svitich; D. A. Nazarov; et al. (Эпидемиология и вакцинопрофилактика)
Relevance. Violation of the regulations on the use of personal protective equipment (PPE) by medical workers when providing medical care to patients with COVID-19 (COVID-19) at their workplaces and in other situations requiring PPE is fraught with serious consequences for the health and life of medical personnel and patients. Aims. To assess the impact of violations in the use of PPE on the incidence of COVID-19 of personnel of medical organizations of various profiles, including when providing medical care to patients with COVID-19. Materials and methods. The study used the method of cross-sectional retrospective simultaneous online questionnaire to assess the effectiveness of preventive measures against the spread of COVID-19, conducted from January to March 2022. The results of an anonymous online survey of various categories of personnel of medical, scientific and educational medical organizations of the Russian Federation providing medical care to patients with COVID-19 (n = 6032 people) were analyzed. Results. The study showed the greatest epidemiological significance in the formation of the risk of SARS-COV-2 infection by the irregular use of masks and gloves in the workplace (when providing medical care). The results of the assessment of the strength of the connection of violations in the use of personal protective equipment with infection with SARS-CoV-2 of the studied groups of personnel are presented. It is shown that the irregular wearing of face masks in the workplace when providing medical care has the most pronounced association with the risk of infection of all the factors studied. It is noted that statistically significantly more often the irregular use of masks and gloves in the workplace was allowed by students and nursing staff. Conclusions. The importance of compliance with the regulations for the use of personal protective equipment by medical workers is shown, not only when providing medical care to patients with COVID-19, but also at home, as well as the impact on the incidence of COVID-19 of the irregularity of the use of PPE by medical personnel in various conditions, including when providing medical care to patients with COVID-19.